1977
DOI: 10.1901/jaba.1977.10-391
|View full text |Cite
|
Sign up to set email alerts
|

EVALUATING MUNICIPAL POLICY: AN ANALYSIS OF A REFUSE‐PACKAGING PROGRAM1

Abstract: The effect of a municipal enforcement program to improve residents' packaging of refuse was analyzed in a multiple-baseline design across two areas of a city. The enforcement program involved instruction concerning refuse-packaging regulations, collection only of appropriately packaged refuse, and feedback notices to residents concerning the reasons for noncollection of their inadequately packaged refuse. Both the number of violations and the percentage of residences violating each day were markedly reduced du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Even so, the consultant group showed significantly more "movement toward" establishing lodges than did the manual group (Fairweather, 1980a, p. 39 Trash-packaging program. After researchers (Stokes & Fawcett, 1977) had experimentally demonstrated that a particular enforcement system was effective in getting city residents to package their trash properly, the new technology was adopted by the city commission passing an ordinance implementing the system (Stokes,Note 4).…”
Section: Examples Of Dissemination and Adoptionmentioning
confidence: 99%
See 3 more Smart Citations
“…Even so, the consultant group showed significantly more "movement toward" establishing lodges than did the manual group (Fairweather, 1980a, p. 39 Trash-packaging program. After researchers (Stokes & Fawcett, 1977) had experimentally demonstrated that a particular enforcement system was effective in getting city residents to package their trash properly, the new technology was adopted by the city commission passing an ordinance implementing the system (Stokes,Note 4).…”
Section: Examples Of Dissemination and Adoptionmentioning
confidence: 99%
“…When the research results showed that the experimental enforcement procedure was successful in improving trash packaging, an implementation plan was developed (Stokes & Fawcett, 1977) jointly by the city management staff and the sanitation workers, who together recommended to the city commission some changes from the procedures used in the research. Prior to adopting the implementation plan, the city commission made some changes of its own.…”
Section: Examples Of Dissemination and Adoptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Issues have included littering (Geller, Winett, & Everett, 1982), trash packaging (Stokes & Fawcett, 1977), city crime (Schnelle, Kirchner, Casey, Uselton, & McNees, 1977), and speeding (Van Houten & Nau, 1983;Van Houten et al, 1985).…”
mentioning
confidence: 99%